Reputation: 65
ABD+ABC+ABCD
I understand that AB is the common factor so I think it becomes:
AB(D+C+CD)
AB(D(1+c)+C)
AB(C+D)
or
AB(D+C+CD)
use commutative law? (i think thats what its called) AB(CD+D+C) AB(C+D)
Please help, I'm very confused with this
Upvotes: 1
Views: 58
Reputation: 118
this is the last step. AB(CD+D+C) => AB(C+D(1+C)) => AB(C+D)
A(1+B)== A(true) .1+B IS always true. this could be thought as (true or expression) which is always true.
Think of the truth table of OR operator.
A B value
0 0 0
0 1 1
1 0 1
1 1 1
here we have value =1 for all the cases where one of the exp =1. Thats all you need.
Commutative law states that A+B=B+A.
This is because truth table of A+B is same as B+A.
Upvotes: 1